Don’t forget the ECG! Coronary occlusion following blunt chest trauma: a case report - Gabsi, Kheira; Cheng, Ernest; Nguyen, Chilan; Abraham, Earl (International Surgery Journal, 2024)
A rare but potentially life-threatening consequence of blunt chest trauma is ST elevation myocardial infarction (STEMI) due to coronary artery occlusion. Here we describe a case of coronary artery occlusion following blunt chest trauma to consider the role of electrocardiography (ECG) and troponin testing as part of the workup of blunt chest trauma.